Resistive Gas Dosimeters as a Novel Method to Measure Small Gas Concentrations and Quantities, Both Accumulative and Timely Resolved - Ralf Moos; Andrea Groß; Daniela Schönauer-Kamin (Proceedings)
Resistive gas dosimeters are a novel method to accurately measure timely intervals like hourly mean values even for small gas concentrations. This measuring principle overcomes the disadvantageously low recovery times of conventional chemiresistive sensors. Applications for the detection of nitrogen oxides in ambient air in the ppb range demonstrate the feasibility.